Undergraduate Student Engagement Theory and Practice in China and the UK - Zhang, Zhe (Springer Singapore, 2018)
This book focuses on undergraduate student engagement in China and the UK. It offers an innovative perspective on this aspect, which, although pervasive, is not always acknowledged by its users to be complex and multidimensional in nature, firmly rooted in cultural, social and disciplinary norms, and difficult to measure. Competition within the global higher education market has become increasingly intense amongst universities; and the higher education sector in China, currently the largest source of international students, is beginning to compete strongly for its home market. Against this consumerist background, student engagement, with its close relation to positive learning outcomes, is increasingly receiving attention from higher education managers and researchers who seek to improve the quality of their 'products'. The research study on which the book is based draws on three courses, two in China and one in the UK. It offers a binary perspective across two very different cultures (Western and Confucian) and two very different subject areas (Chinese language and mathematics). The study employs a mixed-methods design and develops a conceptual framework derived from statistical and thematic analysis. An original theoretical lens, combining a bioecological perspective (Bronfenbrenner) and a sociocultural one (Holland et al.'s Figured Worlds), adds further interpretive power to help understand the construct of student engagement.